English for Nutrition: An ESP-Oriented Need Analysis of Nutrition Students at Pakistani Universities - Asad, Fatima; Irshad, Isra (Pakistan Languages and Humanities Review, 2025)
The study aims to investigate the ESP-based needs of nutrition students at Pakistani Universities. Moreover, it examines the challenges that students encounter in using English. English plays a crucial role in the field of nutrition, as it enables access to scientific knowledge and facilitates participation in professional communication. The study is based on Hutchison and Waters’ model of need analysis, helping us to analyze the needs and wants of the students. This is qualitative research, in which data is collected through interviews with ten students and five faculty members from the nutrition department at the University of Management and Technology. The findings reveal that students struggle with discipline-related reading, comprehension, research writing, and oral communication due to limited English proficiency. It highlights the need for ESP courses based on their academic and professional requirements. This study contributes to curriculum development for nutrition students by identifying the required language skills and professional communication abilities.